Conference Report: DIA/PhRMA workshop on DBS sampling in the pharmaceutical industry: methodology, implementation & best practices. (August 2010) - Evans, Christopher A; Bruce, Christopher; Emmons, Gary T; Gallenberg, Lori; Ji, Qin C; Kinter, Lewis B; Musvasva, Eunice; Wickremsinhe, Enaksha
Representing the first industry-led workshop on this topic, the Drug Information Association (DIA) and Pharmaceutical Research and Manufacturers of America (PhRMA) cosponsored a workshop on dried blood spots (DBS) sampling in the pharmaceutical industry. Sampling from DBS on specialty papers is a novel methodology in the area of pharmacokinetics and toxicokinetics that serves to replace conventional plasma analysis for pharmaceutical development. As the awareness around this technology has increased exponentially in recent years, this 1-day symposium aimed to share current best practices for DBS use and implementation, sample collection, handling and associated bioanalysis. The event drew over 150 industry and agency participants; an impressive attendance for a relatively new technology within the industry. Overall, the day was divided into six separate technical sessions plus poster sessions, and included concurrent breakout sessions dedicated to three key areas surrounding DBS implementation: bioanalytical, toxicology/safety assessment and clinical/pharmacokinetics.